Agility Governance in Implementing Child Friendly Cities in Pekanbaru City in the Special Protection Cluster: Agility Governance Dalam Penerapan Kota Layak Anak Di Kota Pekanbaru Pada Klaster Perlindungan Khusus - chika Chika Amellia; Geovani Meiwanda (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Through the Child Friendly City (KLA) program in the special protection cluster, this study sought to assess the function and agility of the Pekanbaru City government from the perspective of agility governance. It also sought to identify the factors that support the Child Friendly City (KLA) program's implementation in the special protection cluster. In this study, the methods for gathering data were observation, interviews, and documentation. The research was qualitative with a descriptive approach, which involved explaining the research's findings, delving into them to determine how they were arrived at, and drawing conclusions. According to Dowdy & Rieckhoff, the indicators of agile governance theory are Strategy, Structure, Process, and Human Resources, and they are used to provide answers to issue formulation. Because the output of this program is awards, the researchers also looked at the supporting factors for the operation of the program and determined that all indicators on program dexterity measurement have been met. The results of the analysis based on each of the program's dexterity measurement indicators show that the results obtained from the agility governance of the implementation of the Child Friendly Cities program for special protection are agile in their implementation